2022
DOI: 10.5339/qmj.2022.9
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Mortality Rate, Need for ICU Admission and Ventilation in COVID-19 Patients with Diabetes Mellitus

Abstract: Introduction: Coronavirus disease 2019 (COVID-19) has become a threat to public health. People with chronic diseases, such as diabetes, are at a greater risk of severe diseases and death upon contracting this new disease. Due to the novelty of COVID-19, no specific information is available about the degree of its mortality and risk factors among diabetic patients. Therefore, this study aims to compare diabetic and nondiabetic COVID-19 patients regarding mortality rate, the need for intensive care unit (ICU) ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
1
4
1
1
Order By: Relevance
“…In contrast to our results, other studies have with variable certainty reported that T2D is a risk factor for both death from COVID‐19 and admission to an ICU because of COVID‐19 3–11,22 . The discrepancy compared with our results could partly be explained by the higher number of covariates we adjusted for, that could potentially explain the higher risk in patients with T2D.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to our results, other studies have with variable certainty reported that T2D is a risk factor for both death from COVID‐19 and admission to an ICU because of COVID‐19 3–11,22 . The discrepancy compared with our results could partly be explained by the higher number of covariates we adjusted for, that could potentially explain the higher risk in patients with T2D.…”
Section: Discussioncontrasting
confidence: 99%
“…1,2 Since then, studies have found that hospitalized patients with T2D have a higher risk of dying from COVID-19 than patients without T2D. [3][4][5][6][7][8][9][10][11] This has encouraged researchers to explore possible T2Drelated predictors for poor outcomes in COVID-19, such as plasma glucose levels and glucose-lowering medications. [5][6][7]12 Hyperglycaemia in T2D is known to have detrimental effects on immune function, and, to increase inflammatory responses and oxidative stress, ultimately causing microvascular complications.…”
Section: Funding Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, COVID-19 patients who were male, at least 55 years old or had a comorbidity (diabetes mellitus or hypertension), had increased risk of ICU admission. Similar correlations between these factors and ICU admission have been reported [ 5 , 14 – 16 ]. To date, there is no clear explanation why age is an independent risk factor.…”
Section: Discussionsupporting
confidence: 85%
“…Comorbidities, such as hypertension and diabetes, have been reported previously to affect the severity of the disease and the prognosis of COVID-19 patients [ 14 , 26 – 28 ]. Several mechanisms have been discussed for the effect of hypertension, one of which is related to distribution of ACE2 enzyme/receptor, expressed in different tissues, such as lung alveolar epithelial cells, cardiovascular, arterial smooth muscle, arterial and venous endothelial cells, and enterocytes of the small intestine [ 29 ].…”
Section: Discussionmentioning
confidence: 99%